Nanoparticles-based anti-aging treatment of Alzheimer's disease - Jian-Jian Chu; Wen-Bo Ji; Jian-Hua Zhuang; Bao-Feng Gong; Xiao-Han Chen; Wen-Bin Cheng; Wen-Danqi Liang; Gen-Ru Li; Jie Gao; You Yin (Taylor & Francis Group, 2022)
Age is the strongest risk factor for Alzheimer's disease (AD). In recent years, the relationship between aging and AD has been widely studied, with anti-aging therapeutics as the treatment for AD being one of the mainstream research directions. Therapeutics targeting senescent cells have shown improvement in AD symptoms and cerebral pathological changes, suggesting that anti-aging strategies may be a promising alternative for AD treatment. Nanoparticles represent an excellent approach for efficiently crossing the blood-brain barrier (BBB) to achieve better curative function and fewer side effects. Thereby, nanoparticles-based anti-aging treatment may exert potent anti-AD therapeutic efficacy. This review discusses the relationship between aging and AD and the application and prospect of anti-aging strategies and nanoparticle-based therapeutics in treating AD.